Alphabet The Ability To Recognize Letters Of The Alphabet Through Playing With Sand And Plasticine For Children 4-5 Years Old - Ainun Pratiwi (Tajdid Al-Athfal, 2023)
Play activities are children's activities that are carried out throughout the day because for children play is life and life is a game. Early childhood does not distinguish between playing, learning, and working. Children really enjoy the game and always do it wherever they have the opportunity. This study aims to provide data or information as one of the theoretical references to various parties who are competent in early childhood letter recognition research. The playing method carried out in this study used sand and plasticine media. Sand is a small grain that is malleable and fun for children. Plasticine is a toy dough made of flour so that it becomes a soft object so that it can be kneaded, pulled, pressed, and can be shaped according to the child's imagination. Activities using play media can meet all aspects of child development.